2009
DOI: 10.1107/s1600536809028608
|View full text |Cite
|
Sign up to set email alerts
|

N′-(3,4-Dimethoxybenzylidene)acetohydrazide

Abstract: The asymmetric unit of the title compound, C11H14N2O3, contains two independent mol­ecules with close conformations; the C=N—N—C torsion angle is 176.4 (1)° in both mol­ecules. In the crystal, inter­molecular N—H⋯O and C—H⋯O hydrogen bonds link the mol­ecules into chains running along the [01] direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…1. The bond lengths and angles are comparable to those observed for N′-(2,4-dimethoxybenzylidene)-3,4,5-trihydroxybenzohydrazide (Alhadi et al, 2009) and N′-(3,4-dimethoxybenzylidene)acetohydrazide (Zhou et al, 2009). The crystal structure is characterized by chains of running along the c-axis.…”
Section: Data Collectionsupporting
confidence: 73%
See 1 more Smart Citation
“…1. The bond lengths and angles are comparable to those observed for N′-(2,4-dimethoxybenzylidene)-3,4,5-trihydroxybenzohydrazide (Alhadi et al, 2009) and N′-(3,4-dimethoxybenzylidene)acetohydrazide (Zhou et al, 2009). The crystal structure is characterized by chains of running along the c-axis.…”
Section: Data Collectionsupporting
confidence: 73%
“…For related structures see: Alhadi et al (2009); Das & Pal (2004); Tamboura et al (2009); Zhou et al (2009).…”
Section: Related Literaturementioning
confidence: 99%
“…For example, their crystal structures [33][34][35][36][37][38][39][40][41], vibrational analysis [42], antituberculosis activity [43], citotoxicity [44], magnetic properties [45], voltametric behavior [46] and thermochemical study [47] have been reported. However, only a few researches about theoretical study of simple hydrazides have been reported [48,49] and any report about the investigation of tautomerism in AHs has not been observed.…”
Section: Introductionmentioning
confidence: 99%